MEDIA PROMOSI WISATA ALAM PESISIR SELATAN - Rinto Hidayat, Dr. Budiwirman, M.Pd., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Pesisir Selatan in West Sumatra, it is located on the seafront and has large and small uninhabited islands. Maritime and coastal wealth has become a mainstay of tourism in this district. South Coast has 57 islands. There are 17 big islands. The rest are small islands and uninhabited islands in the South Coast, the capital of Pesisir Selatan Regency is Painan. Coastal South has a natural panorama that is quite beautiful and charming. Now this tourist tourism by the central government of Indonesia. As a district that has natural tourist destinations that do not yet have a website. The website is an information and promotion media on the internet with the widest network, media that never stops operating.Designing Media for Promotion of Natural Coastal Areas in South Form o f Web Design This is taken from this nickname of the South Coast district of Million Enchantments. And according to the geography of South Coastal District, South Coastal District is located on the beach, with a coastline of 218 kilometers. The topography consists of plains, mountains and hills which are an extension of the Bukit Barisan cluster. This design uses the SWOT analysis method to look for weaknesses, strengths, opportunities, and threats of the South Coastal District as well as distinguishing factors from competing districts.Designing Media for Promoting Coastal Tourism in the Form of Web Design is a logo, tagline, and icon that is applied to the main media of the Website. Support media stickers, x banners, key chains, t-shirts, glasses, hats, and wall clocks.Keywords: Design, Website, promotion, South Coast.